Drivers of dissolved organic matter processing in subterranean estuaries - Elisa Calvo‐Martin; Xosé Antón Álvarez‐Salgado; María José Pazó Fernández; Vanesa Vieitez Dos Santos; J. Severino P. Ibánhez (Limnology and Oceanography Letters, 2025)
Abstract Subterranean estuaries (i.e., seawater‐fresh groundwater mixing zones at coastal aquifers) are highly reactive boundaries between continental groundwater and coastal surface seawater. Because particulate organic matter is retained in shallow sediments, internal microbial transformations rely on dissolved organic matter (DOM) supply and bioavailability. Here, we investigated DOM carbon content and optical characteristics in two nearby subterranean estuaries with contrasting oxygenation. Coastal organic carbon processing in the anoxic subterranean estuary resulted in the export of DOM enriched in recalcitrant compounds compared to the oxygenated one, which was a net sink of DOM. This contrasting behavior was not driven by opposite redox conditions but from the fast transfer of labile DOM and oxygen to the beach interior of the oxygenated subterranean estuary. There, heterotrophic processes, which rely almost exclusively on DOM, are enhanced, resulting in net DOM consumption prior discharge to surface waters.